Tanduk rusa water extract - a potential natural-based bone stimulus - Azami, Azalea Nur-Qistina; Mokhtar @ Makhtar, Khairani Idah; Mustafa, Basma Ezzat; Mohd. Kenali, Norzaiti; Sha'ban, Munirah; Ahmad, Azlina; Zainol, Ismail (Institute for Medical Research (IMR), Ministry of Health (MOH), Malaysia, 2025)
Tanduk rusa or deer velvet antlers ( has long been utilised in traditional Asian medicine for its various health benefits, including bone health maintenance and regeneration Nonetheless, the fundamental on the scientific merit is still limited This study investigates the effects of DVA extract on stem cells derived from human exfoliated deciduous teeth (capable of differentiating into osteoblasts, which are essential for bone formation and healing to achieve this, the effect of DVA on the biological activity of SHED and its potential to differentiate into osteoblast-like cells were determined accordingly Powdered form of DVA obtained from male Malayan deer (Cervus timorensis) was extracted using sterile water, and its impact on SHED was assessed at different concentrations 0 to 200 µg/ml) Cell viability was determined using MTT assay, cell proliferation using alamarBlue assay, while population doubling time ( was determined according to the available protocol, and morphology were observed under the inverted microscope Osteoblast differentiation was analyzed by measuring alkaline phosphatase ( activity, calcium deposition via Alizarin Red S staining, and expression of osteoblast markers RUNX 2 OSX, and OCN in SHED cultured in osteoblast differentiation medium ( were analysed using RT qPCR Statistical analyses were performed using One way ANOVA and post hoc Tukey’s test with p< 0 05 is considered as significant DVA extract was non toxic to SHED at all tested concentrations, with 3 125 µg/ml identified as the optimal concentration for promoting proliferation and reducing PDT Morphologically, SHED maintained fibroblast like shape at all concentration analysed When cultured in ODM, addition of DVA resulted in increase of ALP activity at Day 21 (P < 0.05) strong calcium mineralization at Day 14 onwards, and higher expression of osteoblast markers RUNX 2 OCN Changes in morphology into osteoblast like was observed DVA stimulates osteoblast differentiation of SHED, particularly during mineralization phases, highlighting its potential as a natural bone development stimulant.